The Effect of Classifying Vocabulary into EFL Student’s Reading Comprehension - Rosa Marianella Contreras-Jordán; María Rossana Ramírez-Ávila (Research in Education and Learning Innovation Archives)
This study examined the effect of classifying vocabulary into parts of speech using Google Drive sheets in order to improve reading comprehension. Participants were 20 EFL stu- dents at a public university in Ecuador whose proficiency level in English was A1 and who were having problems understanding short passages in English. For this action research study, we used quantitative data gathered from pre- and post-surveys, quizzes, and pre- and post-tests. Results from the pre- and post-tests showed that the students improved their word recognition skills by 17% , which enhanced their reading comprehension by 14%. This was corroborated by the p-value =0.000, which shows that the results were due to classifying parts of speech. Additionally, Cohen’s d = 1.02 in the vocabulary section indicates a large impact on learning. However, there was a small effect size (Cohen’s d= 0.39) in reading comprehension. Six quizzes were administered and three of them were compared. These demonstrated a steady improvement in students’ meaning recall and word usage. The results of the survey indicate that the students changed their perspective of learn- ing vocabulary positively after the intervention. The implications of this study can be extended to other EFL teachers in higher education institutions who would like to improve their students’ read- ing comprehension. Future research should evaluate other parts of speech. We also recommend replicating this study with students who have a higher proficiency level in English.